Analisis Komparatif Kepatuhan GRI 300 PT Bumi Resources dan PT Aneka Tambang - Wan Karin Rahmadini; Sania Raza; Tengku Jihan Zahira; Zul Azmi (Jurnal Ekonomi dan Bisnis Digital, 2026)
Sustainability issues have transformed into a central focus in modern business practices, particularly in extractive sectors with high environmental impact risks. This study aims to analyze and compare the compliance level of environmental aspect disclosures based on the Global Reporting Initiative (GRI) 300 standards in the 2024 sustainability reports of PT Bumi Resources Tbk and PT Aneka Tambang Tbk. The research method employed is descriptive comparative using content analysis. Data were obtained through the documentation of official sustainability reports, analyzed using a quantitative scoring system to measure compliance across eight environmental topic standards, ranging from materials (GRI 301) to supplier environmental assessment (GRI 308). The results are expected to provide an empirical overview of the extent to which environmental transparency and accountability are met by mining companies in Indonesia. These findings are anticipated to serve as an evaluative basis for environmental accounting practitioners in improving the quality of non-financial reporting to maintain social legitimacy and stakeholder trust.